Desarrollo emocional en niños de 5 años: Modelos pedagógicos en las nociones básicas en la escuela Azogues, cantón Espíndola, periodo 2023 – 2024. - Correa Guarnizo, Glenda Maribel (2024)
This research analyzes the difficulties of the basic notions that five-year-old children present and the teaching pedagogical model as a cause of them, through the main objective was to analyze the pedagogical model and its influence on the emotional development and the basic notions in 5-year-old children of the Basic Education School "Azogues", it was carried out under a qualitative -quantitative approach, which allowed the collection of both numerical and descriptive data, facilitating the exhaustive analysis and interpretation of the results obtained; Likewise, it has a descriptive scope of a non-experimental cross-sectional type; scientific, inductive, deductive, analytical and synthetic methods were used. The sample consisted of 21 children of preparatory basic education; observation, interview and survey were used as techniques. The results of the interview and observation allowed us to identify that the teacher of the 5-year-old children makes use of pedagogical strategies and resources corresponding to a traditional pedagogical model; Regarding basic notions, it was found that less than half of the students have difficulties in the notions of space, time and laterality. It is concluded that the teacher of five-year-old children applies to a traditional pedagogical model, which negatively influences emotional development and basic notions where children have difficulties in skills such as locating objects and people in relation to themselves and other objects; ordering events in temporal sequence; recognizing the concepts of left, right. Keywords: Child development, basic notions, pedagogical models, teaching practice.